All-optical spatio-temporal control of electron emission from SiO2 nanospheres with femtosecond two-color laser fields - Liu, Qingcao; Zherebtsov, Sergey; Seiffert, Lennart; Skruszewicz, Slawomir; Zietlow, Dominik; Ahn, Seongjin; Rupp, Philipp; Wnuk, Pawel; Sun, Shaohua; Kessel, Alexander; Trushin, Sergei; Schlander, Annika; et al. (New Journal of Physics, 2019)
Field localization by nanostructures illuminated with laser pulses of well-defined waveform enables spatio-temporal tailoring of the near-fields for sub-cycle control of electron dynamics at the nanoscale. Here, we apply intense linearly-polarized two-color laser pulses for all-optical control of the highest energy electron emission from SiO2 nanoparticles. For the size regime where light propagation effects become important, we demonstrate the possibility to control the preferential emission angle of a considerable fraction of the fastest electrons by varying the relative phase of the two-color field. Trajectory based semi-classical simulations show that for the investigated nanoparticle size range the directional steering can be attributed to the two-color effect on the electron trajectories, while the accompanied modification of the spatial distribution of the ionization rate on the nanoparticle surface has only a minor effect.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Dielectric nanospheres; Spatio-temporal control; Two-color laser fields; Ultrafast nanophysics